2011
DOI: 10.1002/cctc.201000320
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Crystal‐Plane Effects of Nanoscale Ceria on the Activity of CuO/CeO2 for NO Reduction by CO

Abstract: The present work elucidated the morphology and crystal‐plane effects of nanoscale ceria on the activity of CuO/CeO2 catalysts toward NO reduction. CeO2 Nanopolyhedra were enclosed by (111) and (100) planes; the nanorods predominantly exposed (110) and (100) surfaces, and the nanocubes only showed the polar (100) planes. Moreover, the strongest interaction was between CuO and CeO2 rods, followed by CuO/CeO2 polyhedra, and the CuO/CeO2 cubes showed the least interaction. Importantly, Cu2+ ions could be incorpora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
197
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(212 citation statements)
references
References 49 publications
(61 reference statements)
10
197
0
2
Order By: Relevance
“…This band has earlier been assigned to Cu 1+ ions in three dimensional clusters of CuO [30]. It is also present in some of the UV-vis spectra of CuO supported by CeO 2 nanorods and polyhedra (but not by ceria cubes) [29]. Unfortunately, Dong et al did not discuss this prominent feature in their spectra.…”
Section: Characterization Of Cuce(x)/shsmentioning
confidence: 97%
See 1 more Smart Citation
“…This band has earlier been assigned to Cu 1+ ions in three dimensional clusters of CuO [30]. It is also present in some of the UV-vis spectra of CuO supported by CeO 2 nanorods and polyhedra (but not by ceria cubes) [29]. Unfortunately, Dong et al did not discuss this prominent feature in their spectra.…”
Section: Characterization Of Cuce(x)/shsmentioning
confidence: 97%
“…5. Compared to CuO/SHS, the ceria-containing samples contain a oxygen-to-Ce 4+ charge-transfer band and an interband transition around 271 and 347 nm, respectively [29]. The samples with Cu/Ce > 1 exhibit a strong and broad absorption band around 700 nm due to the d-d transition of Cu 2+ in octahedral symmetry.…”
Section: Characterization Of Cuce(x)/shsmentioning
confidence: 99%
“…To the best of our knowledge, there have not been any publications for the synthesis of nanorods under such conditions. In most cases, studies have concluded that ceria nanorods are formed at much higher temperatures and pressures [27,[46][47][48][49]. In order to understand the formation of ceria nanorods under microgravitiy condition, two crystal growth processes, Oswald ripening and oriented attachment, can be considered.…”
Section: Transmission Electron Microscopy (Tem)mentioning
confidence: 99%
“…In fact, shapedependent activity of ceria has already been recognized in catalytic CO oxidation [11][12][13][14], NO reduction [15], water-gas shift reaction [16,17] and soot combustion [18]. The energy required to form oxygen vacancies on the {1 1 1} surface of CeO 2 is higher than those on {1 1 0} and {1 0 0} surfaces, so the concentration of oxygen vacancies on differents planes of ceria is different [19].…”
Section: Introductionmentioning
confidence: 99%